Influence of side chain symmetry on the performance of poly(2,5-dialkoxy-p-phenylenevinylene): fullerene blend solar cells - Tuladhar, Sachetan M.; Sims, Marc; Choulis, Stelios A.; Nielsen, Christian B.; George, Wayne N.; Steinke, Joachim H.G.; Bradley, Donal D.C.; Nelson, Jenny (My University, 2009)
We report on studies of poly-(2,5-dihexyloxy-p-phenylenevinylene) (PDHeOPV), a symmetric side-chain polymer, as a potential new donor material for polymer:fullerene blend solar cells. We study the surface morphology of blend films of PDHeOPV with PCBM, the transport properties of the blend films, and the performance of photovoltaic devices made from such blend films, all as a function of PCBM content. In each case, results are compared with those obtained using the asymmetric side chain polymer, poly[2-methoxy-5-(3,7-dimethyloctyloxy)-1,4-phenylenevinylene] (MDMO-PPV), in order to investigate the influence of polymer side chain symmetry on solar cell performance. AFM images show that large PCBM aggregates appear at lower PCBM content (50 wt.% PCBM) for PDHeOPV:PCBM than for MDMO-PPV:PCBM (67 wt.% PCBM) blend films. Time-of-Flight (ToF) mobility measurements show that charge mobilities depend more weakly on PCBM content in PDHeOPV:PCBM than in MDMO:PPV:PCBM, with the result that at high PCBM content the mobilities in PDHeOPV:PCBM are significantly lower than in MDMO:PPV:PCBM blend films, despite the higher mobilities in pristine PDHeOPV compared to pristine MDMO-PPV. Photovoltaic devices show significantly lower power conversion efficiency (0.93%) for PDHeOPV:PCBM (80 wt.% PCBM) blend films than for MDMO-PPV:PCBM (2.2% at 80 wt.% PCBM) blends. This is attributed to the relatively poor transport properties of the PDHeOPV:PCBM blend, which limit the optimum thickness of the photoactive layer in PDHeOPV:PCBM blend devices. The behaviour is tentatively attributed to a higher tendency for the symmetric side-chain polymer chains to aggregate, resulting in poorer interaction with the fullerene and poorer network formation for charge transport.
Keywords: DialkoxyPPV; Fullerene; Side chain symmetry; Bulk heterojunction; Organic photovoltaic; Cells; Charge transport